Case Report: Mixed ductal–lobular carcinoma consisting of invasive lobular carcinoma with a glycogen-rich clear cell pattern and elevated tumor mutation burden - Kawachi, Kae; Tang, Xiaoyan; Kasajima, Rika; Katayama, Kotoe; Yamaguchi, Rui; Yamaguchi, Kiyoshi; Furukawa, Yoichi; Imoto, Seiya; Miyano, Satoru; Yoshioka, Emi; Washimi, Kota; Okubo, Yoichiro; et al. (Frontiers in Oncology, 2026)
BackgroundMixed ductal–lobular carcinoma (MDL) of the breast exhibits considerable molecular complexity. The pathways leading to the glycogen-rich clear cell morphology of the breast tumors, and its clinical relevance, currently remain unclear. Herein, we report a case of MDL, predominantly composed of invasive lobular carcinoma with a glycogen-rich clear cell pattern (gILC), accompanied by classic invasive lobular carcinoma and invasive ductal carcinoma (IDC).Case presentationA 70-year-old woman presented with a 3.5 cm mass in the left breast, for which total mastectomy was performed. The pathological diagnosis was MDL predominantly comprising gILC. Tissue samples from the gILC and IDC areas were subjected to whole-exome and RNA sequencing. The gILC region had a higher tumor mutation burden than the IDC. Three stop-gain single nucleotide variations (SNVs) in CDH1, SETD2, and USP9 and two nonsynonymous SNVs in PIK3CA were identified in the gILC region, whereas only two nonsynonymous SNVs in SMAD4 and PIK3CA were identified in the IDC region. Phylogenetic analysis revealed a common ancestor of gILC and IDC, sharing a pathogenic PIK3CA p.H1047L mutation. Reduced SETD2 protein and H3K36me3 levels and the DNA mismatch repair-microsatellite instability-associated mutational signatures SBS6 and SBS26 were uniquely demonstrated in gILC. Further, a structural variant involving HNF1B and elevated HNF1B transcript levels was detected in gILC. The predominant gILC component was estrogen receptor-positive. Adjuvant endocrine therapy was administered postoperatively, and the patient currently remains disease-free at 51 months.ConclusionIn this case, the gILC and IDC components of an MDL shared a common origin, but exhibited marked genomic divergence. This experience also shows that SETD2 functional impairment may underlie gILC hypermutation, while HNF1B overexpression could contributes to a glycogen-rich clear cytoplasm. Overall, this case emphasizes the complexity of MDL with gILC, and highlights the need for further studies to clarify the underlying molecular mechanisms and their prognostic implications.